STUDIES ON BIOLOGY OF A NEW STRAIN (K2) OF SILKWORM (BOMBYX MORI L.) UNDER DIFFERENT SETS OF TEMPERATURE AND HUMIDITY - S. Kaleem; I. Mahmood; M. Ahmad; M. A. A. H. A. Bukhsh; A. Wasaya; A. Qayyum; M. A. Raza (Journal of Animal and Plant Sciences, 2011)
Silkworm rearing is an applied science based on theory of anatomical physiology of silkworm and silk worm diseases. With an ultimate aim of producing more and better quantity and quality of silk (a natural protein fiber) and to expand the areas for its production country wise regions, many strains have been introduced date to date. A new strain of silkworm (K2) was evaluated to include it in the efforts to raise our national productive potential of natural silk. For this purpose the biology of this strain was determined under different sets of temperature and humidity. The study was carried out in the old insectary, Department of Agri. Entomology, University of Agriculture, Faisalabad, Pakistan. The eggs of silkworm were brought from Directorate of Sericulture, Muzaffarabad, Azad Jammu & Kashmir. The eggs were shifted to four different sets of temperatures, 30, 25, 20oC and at room temperature as reference. The relative humidity (R.H) 60, 70 and 80% for first three temperatures was maintained, respectively. In each group equal number of larvae was placed and groups were assigned as: To = Room Temperature and R. H., T1 = 30oC with 60% R. H., T2 = 25oC with 70% R. H. and T3 = 20oC with 80% R. H. The experiment was laid out in completely randomized design. It was observed that the longest period (4440 minutes) during first instar was taken when silkworm larvae were subjected to 20oC and 80 % R.H, where as the shortest period (2010 minutes) was recorded when silkworm larvae were subjected to 30oC and 60 % R.H. The longest moulting period after first instar (1680 minutes) was recorded in control and the shortest period (1270 minutes) was observed when larvae were subjected to 30oC and 60% R.H. The longest period for second instar was 4560 minutes where as the shortest period (2876.66 minutes) was recorded when larvae were subjected to 30oC and 60% R.H. The longest moulting period (1620 minutes) after second instar was recorded when larvae were subjected to 20oC and 80% R.H. and the shortest period (1438.33 minutes) was observed when larvae were subjected to 30oC and 60% R.H. The longest period for the third instar (6662.07 minutes) was observed when larvae were subjected to 20oC and 80% R.H, where as the lowest period (4305 minutes) was observed when larvae were subjected to 30oC and 60 % R.H. The longest period for the moulting after third instar (2760 minutes) was observed when larvae were subjected to 20oC and 80% R.H., where as the lowest period (1437 minutes) was noted when larvae were subjected to 30oC and 60% R.H. The longest period of fourth instar (7413.33 minute) was observed when larvae were subjected to 20oC and 80% R.H.; where as the lowest period (4318.33 minutes) was noted when larvae were subjected to 25oC and 70% R.H. The longest period for the moulting period after fourth instar (2520 minutes) was observed when larvae were subjected to 20oC and 80% R.H., where as the lowest period (1613.33 minutes) was noted when larvae were subjected to 30oC and 60% R.H. The longest period for fifth instar (13010 minutes) was observed when larvae were subjected to 20oC and 80% R.H.; where as the lowest period (10080 minutes) was noted when larvae were subjected to 25oC and 70% R.H. The longest period for total life (44635 minutes) was observed when larvae were subjected to 20oC and 80% R.H.; where as the shortest period (29650 minutes) was noted when larvae were subjected to 30oC and 60% R.H.
Keywords: Silkworm; new strain; biology; temperature; relative humidity.